Triad-type, multi-functional compatibilizers for enhancing efficiency, stability and mechanical robustness of polymer solar cells. Issue 27 (2nd July 2020) - Kim, Geon-U.; Lee, Young Woong; Ma, Boo Soo; Kim, Jinseck; Park, Jin Su; Lee, Seungjin; Nguyen, Thanh Luan; Song, Myoung; Kim, Taek-Soo; Woo, Han Young; Kim, Bumjoon J.
Abstract : Our work highlights the importance of A–D–A triad type, multi-functional compatibilizer for enhancing device efficiency, thermal stability and mechanical robustness of polymer solar cells, suggesting design guidelines for molecular compatibilizers. Abstract : The operation stability of polymer solar cells (PSCs) is one of the most important prerequisites for their practical use. In this work, we report a new acceptor–donor–acceptor (A–D–A) triad-type small molecule, 5TRh-PCBM, as a compatibilizer for enhancing the thermal stabilities and mechanical properties of efficient PSCs while increasing their power conversion efficiencies (PCEs). This multifunctional 5TRh-PCBM molecule, consisting of an oligothiophene segment as the central core and fullerene derivatives as the end groups, is designed to enable strong interactions between the 5TRh-core with various types of efficient polymer donors containing thiophene or fused-thiophene units, while the end fullerene groups preferentially interact with PCBM acceptors. To examine the effectiveness of this molecular compatibilizer, PSCs with different donors (PTB7-Th, PBDB-T, and P3HT ) have been fabricated and tested, with addition of various amounts of 5TRh-PCBM . The addition of 5 and 10 wt% of 5TRh-PCBM significantly enhances the thermal and mechanical stabilities of all tested PSCs. Importantly, unlike typical compatibilizers, the addition of 5TRh-PCBM can increase the PCEs of the PSCs due to its light harvesting capability. In particular, the PCE of PTB7-Th :PCBM -based PSCs is increased from 9.37% to 10.09% with the 5 wt% addition of 5TRh-PCBM . Our comprehensive investigations have revealed the effects of 5TRh-PCBM on the optical, morphological, photovoltaic, and mechanical properties of molecularly engineered PSCs.